Knowledge Regarding Coronavirus Disease-19 Related to Nutritional Practices in Residents of Medan City, Indonesia - Natalia, Debora; Sari, Dina Keumala; Ardiansyah, Rizky; Fadinie, Wulan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The coronavirus disease 2019 (COVID-19) is a new type of disease, which has never been identified in humans. Some of the primary symptoms are associated with acute respiratory disorders, namely, fever, cough, and shortness of breath. A person’s nutritional status affects the risk of infection and the clinical course of COVID-19. Knowledge is an important domain for the formation of a person’s behavior, because actions based on knowledge are more important than actions or behaviors that are not based on knowledge. AIM: This study aims to determine the relationship between the level of knowledge about COVID-19 and the balanced nutritional behavior of the people of Medan City. METHODS: This was a descriptive analytical study, with a cross-sectional research design. The study samples consisted of Medan City residents, who met the inclusion and exclusion criteria based on the convenient sampling method. The primary data in this study were drawn from a research questionnaire, which was filled out online. RESULTS: From 200 of the research samples analyzed, 88% had a good level of knowledge towards COVID-19, 59% had a good level of nutrition practices. There was no significant difference between mean score and results for knowledge of COVID-19 and nutritional practices based on certain demographic characteristics. The relationship analysis showed p = 0.22; prevalence ratio = 2.711; and confidence interval 95%= 1.123–6.541 with a correlation value of 0.161. CONCLUSIONS: There was a weak positive relationship between knowledge regarding COVID-19 and nutritional practices in residents of Medan City, Indonesia.